Method for testing flexibility of negative plate

Through a test method based on patterned tooling and weight difference analysis, the subjective problem of negative electrode sheet flexibility detection in the prior art is solved, fast and accurate flexibility detection and better screening of adhesive formulas are achieved, and the safety and service life of lithium-ion batteries are improved.

CN119757104AActive Publication Date: 2025-04-04SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411906437.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The method used in the prior art to judge the flexibility of the negative electrode sheet of lithium-ion battery has great subjectivity, lacks objective quantification standards, and cannot quickly and accurately detect the flexibility of the negative electrode sheet.

Method used

A method for testing the flexibility of the negative electrode sheet is provided. By weighing the weight of the electrode sheet to be tested, scraping off part of the negative electrode active material layer according to the preset pattern, repeatedly scraping, calculating the weight difference after each scraping, and drawing a comparison ring through data analysis to judge the flexibility of the electrode sheet to be tested.

Benefits of technology

It reduces the uncertainty of subjective judgment, improves the consistency and accuracy of test operations, can quickly and accurately judge the flexibility of the negative electrode sheet, and screen out better adhesive formulas through quantitative analysis, thereby improving the safety and service life of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119757104A_ABST
    Figure CN119757104A_ABST
Patent Text Reader

Abstract

The invention provides a negative plate flexibility testing method. The method comprises the following steps: S1, weighing the weight of a to-be-measured pole piece, and recording the weight as m0; s2, scraping a partial region of a negative electrode active material layer in the to-be-measured pole piece according to a preset pattern, weighing the weight of the to-be-measured pole piece after scraping, and recording the weight as m1; s3, repeating the step S2 for n-1 times, scraping the areas with the same shape each time, sequentially obtaining m2 to mn, and respectively calculating the weight difference between two adjacent times of weighing; step S4, drawing by taking the formula of the binder as a horizontal axis and the weight difference as a longitudinal axis, drawing the data points corresponding to the weight difference obtained in the step S3 in the drawing, drawing a comparison ring by taking an absolute value of a difference value between an upper limit value and a lower limit value of a 95% confidence interval of the data point corresponding to each formula as a diameter, and the flexibility of the pole piece to be detected is judged by analyzing the position of the comparison ring in the graph. According to the test method, the flexibility of the lithium ion battery negative plate can be rapidly and accurately detected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a method for testing the flexibility of a negative electrode sheet. Background Art

[0002] Lithium-ion batteries have become an indispensable component in the fields of mobile electronic devices, electric vehicles and energy storage systems due to their high energy density, long cycle life and excellent performance. With the improvement of global awareness of environmental protection and the emphasis on battery safety and cost control, the trend of using water-based binders to replace traditional organic solvent binders is becoming increasingly obvious. Water-based binders have become the preferred solution for the preparation of lithium-ion battery negative electrode sheets due to their environmental friendliness, high safety and low cost.

[0003] Aqueous binders such as polymer gels, nanoparticles, and polymer dispersions have been widely studied due to their specific performance advantages. These binders have advantages in improving battery performance, especially in improving battery cycle stability and electrochemical performance. However, commonly used aqueous binders such as sodium methylcellulose (CMC) and styrene-butadiene rubber latex (SBR) have certain limitations in the preparation of pole pieces. Under the influence of temperature and humidity, the coating of the material area of ​​the pole piece is prone to cracking or peeling, which not only affects the production efficiency of the battery, but also causes serious material loss during the slitting and winding process of the pole piece, thereby causing safety hazards to the battery and reducing the overall performance of the battery.

[0004] Polyacrylic acid (PAA) has excellent adhesion and ionic conductivity, which can enhance the bonding force between the negative electrode material and the current collector and increase the contact area, thereby reducing the internal resistance of the battery and improving the transmission efficiency of lithium ions. However, the molecular chain of PAA is relatively rigid and brittle, which can easily cause the pole piece to lose powder during the slitting and winding process. When the pole piece is subjected to external force, the PAA coating is more likely to undergo irreversible deformation, resulting in the agglomeration of active materials and the decline of battery performance. To solve the above problems, it is usually necessary to modify the PAA chain segment or compound it with other commonly used binders to improve the flexibility of the negative electrode sheet and enhance the safety and service life of the battery.

[0005] At present, the method used to judge the flexibility of lithium-ion battery negative electrode sheets mainly relies on the peel strength test, that is, the negative electrode sheet coating is torn off with tape, and then the peeling of the coating is observed by naked eyes to judge the flexibility of the negative electrode sheet. However, the judgment criteria of the above method are limited by the subjectivity of the operator and lack objective quantitative indicators, making it difficult to accurately compare and screen between different binder formulations.

[0006] In summary, researching and developing a fast, accurate and quantifiable test method for the flexibility of lithium-ion battery negative electrode sheets is of great significance for quantitatively analyzing the effects of different binder formulations on the flexibility of negative electrode sheets, and for screening out better binder formulations to improve the safety and service life of lithium-ion batteries. Summary of the invention

[0007] The main purpose of the present invention is to provide a method for testing the flexibility of negative electrode sheets to solve the problem that the testing methods in the prior art are highly subjective, lack objective quantitative standards, and cannot quickly and accurately detect the flexibility of negative electrode sheets of lithium-ion batteries.

[0008] In order to achieve the above-mentioned object, the present invention provides a method for testing the flexibility of a negative electrode sheet, the method comprising: step S1, weighing the weight of the electrode sheet to be tested, recorded as m0; the electrode sheet to be tested comprises a negative electrode current collector and a negative electrode active material layer arranged on the surface thereof, and the material of the negative electrode active material layer comprises a binder; step S2, scraping off a part of the negative electrode active material layer according to a preset pattern, weighing the weight of the electrode sheet to be tested after scraping, recorded as m1; step S3, repeating step S2 n-1 times, wherein n ≥ 5, and scraping off an area of ​​the same shape each time, and obtaining m2 to m1 in turn. n , respectively calculate the weight difference between two adjacent weighings; step S4, draw a graph with the binder formula as the horizontal axis and the weight difference as the vertical axis, plot the data points corresponding to the weight difference obtained in step S3 in the graph, draw a comparison ring with the absolute value of the difference between the upper limit and the lower limit of the 95% confidence interval of the data point corresponding to each formula as the diameter, and judge the flexibility of the electrode to be tested by analyzing the position of the comparison ring in the graph.

[0009] Furthermore, step S2 further includes: placing the patterning device on the surface of the negative electrode active material layer in the electrode to be tested, and scraping the negative electrode active material layer with a scratching needle.

[0010] Furthermore, the patterned chemical device has at least one groove structure; preferably, the number of the groove structures is 5 to 10, and the width is 0.5 to 2 mm.

[0011] Furthermore, the groove structure is selected from strip grooves and / or arc grooves; preferably, the length of the strip groove is 3 to 10 cm, and the arc groove is a semicircular groove, and more preferably its radius is 2 to 5 cm.

[0012] Furthermore, the material of the patterned chemical suit is selected from polymethyl methacrylate and / or polytetrafluoroethylene.

[0013] Furthermore, the shape of the electrode to be tested is a rectangle or a square, with a length of 7 to 20 cm, a width of 7 to 20 cm, or a side length of 7 to 20 cm.

[0014] Furthermore, the intersection area of ​​the comparison rings corresponding to the two pole pieces to be tested is analyzed to determine the difference in flexibility of the pole pieces to be tested.

[0015] Furthermore, the scribing needle has a conical tip, and the diameter of the tip does not exceed the width of the groove structure; preferably, the material of the scribing needle is selected from stainless steel and / or aluminum.

[0016] Furthermore, step S2 also includes: using an ear cleaning ball to remove the scraped powder; preferably, the cleaning process includes: blowing along the scraping direction of the electrode to be tested for 3 to 5 times, and then blowing perpendicular to the scraping direction for 3 to 5 times.

[0017] Furthermore, data analysis software is used to draw comparison circles. Preferably, the data analysis software is JMP software, and the variance analysis function in the JMP software is used to draw comparison circles.

[0018] Furthermore, the surface density of the negative electrode active material layer in the electrode to be tested is 5 to 15 mg / cm 2 , compacted density is 1~1.7mg / cm 3 .

[0019] By applying the technical solution of the present invention, compared with the traditional peel strength test, the test method for the flexibility of the negative electrode sheet provided by the present application uses the weight difference before and after the negative electrode sheet is scraped as an objective indicator to quantify the flexibility of the negative electrode sheet, which can reduce the uncertainty of subjective judgment. Limiting the shape of the scraped area each time to the same shape can improve the consistency of the test operation process and reduce errors; by analyzing the comparison ring drawn by the data points corresponding to the weight difference, the flexibility of the negative electrode sheet can be quickly and accurately determined. By quantitatively analyzing the effects of different ratios of binder formulas on the flexibility of the negative electrode sheet, a better binder formula can be screened, thereby improving the processability of the negative electrode sheet of the lithium-ion battery and improving the safety and service life of the lithium-ion battery.

[0020] In summary, the test method for the flexibility of the negative electrode sheet provided in the present application is simple to operate, easy to implement, and convenient for batch screening, thereby facilitating the industrial production of negative electrode sheets. At the same time, a better binder formula can be screened out based on the test results, thereby improving the electrochemical performance, cycle performance and safety of the negative electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0022] Figure 1 A top view of a patterned device in one embodiment of the present application is shown;

[0023] Figure 2 The data points and comparison circles corresponding to the weight differences measured by Examples 1 to 3 of the present application are shown;

[0024] Figure 3 The data points and comparison circles corresponding to the weight differences measured by Examples 4 to 6 of the present application are shown;

[0025] Figure 4 The figure shows the material drop situation of the crease area of ​​the electrode to be tested in Comparative Example 1 of the present application;

[0026] Figure 5 The figure shows the material drop situation of the crease area of ​​the electrode to be tested in Comparative Example 2 of the present application;

[0027] Figure 6 The figure shows the material shedding situation in the crease area of ​​the pole piece to be tested in comparative example 3 of the present application. DETAILED DESCRIPTION

[0028] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0029] As described in the background technology, the existing test methods for the flexibility of negative electrode sheets are highly subjective and lack objective quantitative standards, and are unable to quickly and accurately detect the flexibility of negative electrode sheets of lithium-ion batteries. In order to solve the above technical problems, the present application provides a test method for the flexibility of negative electrode sheets, the test method comprising: step S1, weighing the weight of the electrode sheet to be tested, recorded as m0; the electrode sheet to be tested comprises a negative electrode current collector and a negative electrode active material layer disposed on its surface, and the material of the negative electrode active material layer comprises a binder; step S2, scraping off a portion of the negative electrode active material layer according to a preset pattern, weighing the weight of the electrode sheet to be tested after scraping, recorded as m1; step S3, repeating step S2 n-1 times, where n ≥ 5, and scraping off the area of ​​the same shape each time, and obtaining m2 to m1 in turn. n , respectively calculate the weight difference between two adjacent weighings; step S4, draw a graph with the binder formula as the horizontal axis and the weight difference as the vertical axis, plot the data points corresponding to the weight difference obtained in step S3 in the graph, draw a comparison ring with the absolute value of the difference between the upper limit and the lower limit of the 95% confidence interval of the data point corresponding to each formula as the diameter, and judge the flexibility of the electrode to be tested by analyzing the position of the comparison ring in the graph.

[0030] It should be noted that the absolute value of the difference between the upper limit and the lower limit of the 95% confidence interval in this application is proportional to the inverse of the square root of the number of weighing times, and its specific value is determined by the variance analysis function (ANOVA test) in JMP software (interactive data analysis software developed by CS Software).

[0031] In the above-mentioned negative electrode sheet flexibility test method provided in the present application, the electrode sheet to be tested is a negative electrode sheet with a laminated structure, and its laminated structure is a negative electrode active material layer / negative electrode current collector layer. Compared with the traditional peel strength test, the present application uses the weight difference before and after the negative electrode sheet is scraped as an objective indicator to quantify the flexibility of the negative electrode sheet, which can reduce the uncertainty of subjective judgment. Limiting the shape of the scraped area each time to the same shape can improve the consistency of the test operation process and reduce errors; by analyzing the comparison ring drawn by the data points corresponding to the weight difference, the flexibility of the negative electrode sheet can be quickly and accurately determined. By quantitatively analyzing the effects of binder formulations with different ratios on the flexibility of the negative electrode sheet, a better binder formulation can be screened out, thereby improving the processability of the negative electrode sheet of the lithium-ion battery and improving the safety and service life of the lithium-ion battery.

[0032] In the above-mentioned negative electrode sheet flexibility test method provided in the present application, a graph is drawn with the binder formula as the horizontal axis and the weight difference as the vertical axis. The lower the position of the comparison ring drawn by the weight difference data points in the graph, the better the flexibility of the electrode sheet to be tested corresponding to the comparison ring, and the better the binder formula.

[0033] In summary, the test method for the flexibility of the negative electrode sheet provided in the present application is simple to operate, easy to implement, and convenient for batch screening, thereby facilitating the industrial production of negative electrode sheets. At the same time, a better binder formula can be screened out based on the test results, thereby improving the electrochemical performance, cycle performance and safety of the negative electrode sheet.

[0034] In a preferred embodiment, step S2 further comprises: Figure 1 The patterned chemical device shown is placed on the surface of the negative electrode active material layer in the electrode to be tested, and the negative electrode active material layer is scraped with a scratching needle. Compared with other methods, the above method is conducive to improving the consistency and accuracy of the scraping process, and is conducive to reducing operating errors, thereby improving the accuracy of the test results.

[0035] In a preferred embodiment, Figure 1 As shown, the patterned chemical equipment has at least one groove structure. The groove structure in the present application is a groove structure that runs through from top to bottom, so that it is convenient to use a stylus to scrape the negative electrode active material layer in the target area of ​​the groove structure. Compared with other structures, the use of the patterned chemical equipment with the above structure can ensure that the target area scraped each time is the same depth and width, which is conducive to improving the consistency of the scraping process, helping to reduce operational errors, and thus helping to improve the accuracy of the test results.

[0036] In order to further reduce operational errors, further improve the accuracy of test results, and further improve the consistency of the scraping process, preferably, the number of the groove structures is 5 to 10, and the width is 0.5 to 2 mm.

[0037] In order to simulate different stress conditions (such as torque, etc.) that the negative electrode sheet may encounter during the preparation process (such as slitting and winding), thereby providing multiple dimensions for testing the flexibility of the negative electrode sheet and thereby improving the accuracy of the test results, in a preferred embodiment, the groove structure includes but is not limited to strip grooves and / or arc grooves.

[0038] In order to further simulate different stress conditions that the negative electrode sheet may encounter during the preparation process, thereby further improving the accuracy of the test method for the flexibility of the negative electrode sheet, preferably, the length of the strip groove is 3 to 10 cm, and the arc groove is a semicircular groove with a radius of 2 to 5 cm.

[0039] In a preferred embodiment, the material of the patterned chemical coating includes but is not limited to polymethyl methacrylate (PMMA) and / or polytetrafluoroethylene (PTFE). Compared with other materials, the patterned chemical coating made of the above materials is beneficial to reducing the additional damage caused by the patterned chemical coating to the electrode to be tested, thereby reducing the operation error and improving the accuracy of the test result. On the other hand, it is beneficial to improve the rigidity of the patterned chemical coating, thereby preventing it from deforming due to force during the scraping process.

[0040] In a preferred embodiment, the shape of the electrode to be tested is rectangular or square, with a length of 7 to 20 cm, a width of 7 to 20 cm, or a side length of 7 to 20 cm. The shape and size of the electrode to be tested include but are not limited to the above ranges. Limiting it to the above ranges is convenient for placing the above pattern chemical equipment provided by the present application on the surface of the electrode to be tested for scraping, and is also conducive to providing more test areas, so as to facilitate multiple scrapings, thereby helping to reduce operational errors.

[0041] In a preferred embodiment, the intersection area of ​​the comparison rings corresponding to the two pole pieces to be tested is analyzed to determine the difference in the flexibility of the pole pieces to be tested. By analyzing and comparing the intersection areas of the comparison rings corresponding to different pole pieces to be tested, the difference in the flexibility of different pole pieces to be tested can be obtained. The larger the intersection area, the smaller the difference in the flexibility of the corresponding pole pieces to be tested. When the intersection area is zero, it indicates that the flexibility of the corresponding pole pieces to be tested has a significant difference. Compared with other methods, the above method is conducive to a more intuitive comparison of the differences in the flexibility of different negative pole pieces.

[0042] In order to further improve the consistency of the scraping process, further reduce operational errors during the test process, and thus further improve the accuracy of the test results, in a preferred embodiment, the scratching needle has a conical tip, and the diameter of the tip does not exceed the width of the groove structure.

[0043] In order to reduce the additional damage caused by the scratching needle to the negative electrode sheet, thereby further reducing the operational errors during the test process, and also to improve the rigidity of the scratching needle and inhibit its deformation due to force during the scraping process, preferably, the material of the scratching needle includes but is not limited to stainless steel and / or aluminum, preferably, the stainless steel includes but is not limited to 304 stainless steel and / or 316 stainless steel.

[0044] In a preferred embodiment, step S2 also includes: using an ear cleaning ball to remove the scraped powder; the preferred cleaning process includes: blowing 3 to 5 times along the scraping direction of the electrode to be tested, and then blowing 3 to 5 times perpendicular to the scraping direction. The scraped powder includes the powder scraped in the target scraping area, and the powder that falls around the target scraping area due to the interaction force (such as the cohesion, adhesion and friction of the negative electrode active material layer). Compared with other methods, the above method is conducive to improving the removal rate of the scraped powder, thereby helping to reduce the operating errors during the test process, and then helping to improve the accuracy of the test results.

[0045] In order to improve the accuracy of data analysis and thus further improve the accuracy of test results, in a preferred embodiment, data analysis software is used to draw comparison rings. Preferably, the data analysis software is JMP software (interactive data analysis software developed by CS Software), and the variance analysis function in the JMP software is used to draw comparison rings.

[0046] In a preferred embodiment, the surface density of the negative electrode active material layer in the electrode to be tested is 5 to 15 mg / cm 2 , compacted density is 1~1.7mg / cm 3 The surface density and compaction density of the negative electrode active material layer in the electrode to be tested include but are not limited to the above ranges. Limiting them within the above ranges is conducive to improving the consistency of the electrode to be tested, thereby improving the accuracy of the test, and further facilitating more accurate analysis of the flexibility of the electrode to be tested to screen out a better binder formula.

[0047] In order to improve the consistency of the prepared electrode sheets to be tested, thereby improving the accuracy of the test method for the flexibility of the negative electrode sheets, and then facilitate screening out a better binder formula by comparing the flexibility of the negative electrode sheets, in a preferred embodiment, the preparation method of the electrode sheets to be tested includes: mixing the negative electrode active material, the conductive agent and the binder to obtain a negative electrode slurry; coating the negative electrode slurry on the surface of the current collector, and obtaining the electrode sheet to be tested after rolling and drying.

[0048] In order to improve the processability of the electrode to be tested, and to further improve the consistency of the prepared electrode to be tested, thereby further improving the accuracy of the test method for the flexibility of the negative electrode, preferably, the weight ratio of the negative electrode active material, the conductive agent and the binder is (85~95):(1~5):(2~5).

[0049] In a preferred embodiment, the temperature of the rolling process is 25-150°C, the pressure is 3-10t, and the number of rolling times is 1-3 times. The temperature, pressure and number of rolling times of the rolling process include but are not limited to the above ranges. Limiting them to the above ranges is conducive to improving the efficiency of the rolling process, and is also conducive to improving the consistency of the prepared electrode to be tested, thereby helping to improve the accuracy of the test results.

[0050] In a preferred embodiment, the drying process is vacuum drying, the vacuum drying temperature is 80-120°C, the vacuum degree is ≤-0.09MPa, and the time is 8-12h. The temperature, vacuum degree and time of the drying process include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the efficiency of the drying process, and is also conducive to improving the consistency of the prepared electrode to be tested, thereby helping to improve the accuracy of the test results.

[0051] In order to improve the machinability of the negative electrode sheet of the lithium ion battery and inhibit the falling of the negative electrode sheet during processing, thereby improving the safety and service life of the lithium ion battery, in a preferred embodiment, the binder includes at least three different types of binders; preferably, the binder includes but is not limited to at least three of the group consisting of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, polyvinyl alcohol and sodium alginate.

[0052] In order to further improve the machinability of the negative electrode sheet of the lithium-ion battery, further suppress the material falling of the negative electrode sheet during processing, thereby further improving the safety and service life of the lithium-ion battery, preferably, the composite binder is a combination of sodium carboxymethyl cellulose, styrene-butadiene rubber and polyacrylic acid, and the weight ratio of the three is (0.1-2.5):(0.1-5):(0.1-5).

[0053] The above-mentioned negative electrode sheet flexibility testing method provided in the present application is applicable to negative electrode sheets made of negative electrode active materials commonly used in the art. In a preferred embodiment, the negative electrode active materials include but are not limited to one or more of the group consisting of graphite, silicon-carbon materials and silicon-oxygen materials.

[0054] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0055] Example 1

[0056] A method for testing the flexibility of a negative electrode sheet comprises the following steps:

[0057] (1) Preparation of the electrode to be tested: Graphite, conductive carbon black, sodium carboxymethyl cellulose binder, styrene-butadiene rubber binder and polyacrylic acid binder in a weight ratio of 94:2.5:1:2:0.5 were mixed to obtain a negative electrode slurry; the negative electrode slurry was coated on the surface of copper foil, rolled once at 25°C and 5t pressure, and then dried in a vacuum oven at 80°C for 12h, and 2.8g (m0) of the electrode to be tested was obtained by weighing; wherein the laminated structure of the electrode to be tested is a negative electrode active material layer / copper foil, the shape is rectangular, and its length is 20cm, the width is 10cm, and the surface density of the negative electrode active material layer is 8.6mg / cm 2 , compacted density is 1.5mg / cm 3 ;

[0058] (2) Place a patterned chemical device (having 5 strip grooves, each of which is 6 cm long, 0.5 mm wide, and made of PMMA) on the surface of the negative electrode active material layer in the electrode to be tested, and use a 304 stainless steel stylus to scrape the 5 strip grooves in the patterned chemical device until the copper foil is exposed; use an ear-washing bulb to blow 3 times along the scraping direction, and then blow 3 times perpendicular to the scraping direction to remove the powder scraped from the inside and around the grooves; after completion, weigh the scraped electrode to be tested to obtain m1;

[0059] (3) Move the patterned chemical device and place it on the surface of the negative electrode active material layer that has not been scraped off, repeat step (2) four times, and obtain m2, m3, m4 and m5 in sequence; calculate the weight difference between two adjacent weighings, and the specific weight difference data is shown in Table 1;

[0060] (4) Import the weight difference data points obtained in step (3) into the JMP software, plot a graph with the binder formula as the horizontal axis and the weight difference as the vertical axis, and draw a comparison ring using the variance analysis function in the JMP software. The lower the position of the comparison ring in the graph, the better the flexibility of the corresponding electrode to be tested.

[0061] Example 2

[0062] The difference from Example 1 is that the formula of the binder of the electrode to be tested is different, wherein the weight ratio of sodium carboxymethyl cellulose, styrene-butadiene rubber and polyacrylic acid is 1:2:1, and the remaining steps are the same as Example 1.

[0063] Example 3

[0064] The difference from Example 1 is that the formula of the binder of the electrode to be tested is different, wherein the weight ratio of sodium carboxymethyl cellulose, styrene-butadiene rubber and polyacrylic acid is 1:2:2, and the remaining steps are the same as Example 1.

[0065] The data points corresponding to the weight differences measured in Examples 1 to 3 and the comparison rings are as follows: Figure 2 As shown. Figure 2 It can be seen that the position of the comparison ring corresponding to the adhesive formula of the electrode to be tested in Example 1 is the lowest, indicating that the flexibility of the electrode to be tested in Example 1 is the best; by observing the intersection area of ​​the comparison rings corresponding to Examples 1 to 3, it can be seen that the intersection area of ​​the comparison rings of Example 2 and Example 1 is larger, while the intersection area of ​​the comparison rings of Example 3 and Example 1 is smaller, indicating that compared with Example 1, the flexibility of the electrode to be tested in Example 2 is not significantly reduced, while the flexibility of the electrode to be tested in Example 3 is significantly reduced.

[0066] On the premise that the flexibility of the electrode to be tested in Example 2 is not significantly reduced compared with Example 1, the polyacrylic acid content in the binder formula of the electrode to be tested in Example 2 is higher, and the dynamic performance of the negative electrode is better, so the binder formula corresponding to Example 2 is the optimal formula.

[0067] Example 4

[0068] A method for testing the flexibility of a negative electrode sheet comprises the following steps:

[0069] (1) Preparation of the electrode to be tested: Graphite, conductive carbon black, sodium carboxymethyl cellulose binder, styrene-butadiene rubber binder and polyacrylic acid binder in a weight ratio of 94:2.5:1:2:0.5 were mixed to obtain a negative electrode slurry; the negative electrode slurry was coated on the surface of copper foil (the coating device used was different from that in Example 1), rolled once at 25°C and 5t pressure, and then dried in a vacuum oven at 80°C for 12h, and 2.1g (m0) of the electrode to be tested was obtained by weighing; wherein the laminated structure of the electrode to be tested was a negative electrode active material layer / copper foil, the shape was rectangular, and its length was 20cm, the width was 10cm, and the surface density of the negative electrode active material layer was 5.1mg / cm 2 , compacted density is 1.2mg / cm 3 ;

[0070] (2) Place a patterned chemical device (having 5 semicircular grooves, each with a width of 0.5 mm and a radius of 2 cm, and made of PMMA) on the surface of the negative electrode active material layer in the electrode to be tested, and use a 304 stainless steel stylus to scrape the 5 semicircular grooves in the patterned chemical device until the copper foil is exposed; use an ear-washing bulb to blow 3 times along the scraping direction, and then blow 3 times perpendicular to the scraping direction to remove the powder scraped from the inside and around the grooves; after completion, weigh the scraped electrode to be tested to obtain m1;

[0071] (3) Move the patterned chemical device and place it on the surface of the negative electrode active material layer that has not been scraped off, repeat step (2) four times, and obtain m2, m3, m4 and m5 in sequence; calculate the weight difference between two adjacent weighings, and the specific weight difference data is shown in Table 1;

[0072] (4) Import the weight difference data points obtained in step (3) into the JMP software, plot a graph with the binder formula as the horizontal axis and the weight difference as the vertical axis, and draw a comparison ring using the variance analysis function in the JMP software. The lower the position of the comparison ring in the graph, the better the flexibility of the corresponding electrode to be tested.

[0073] Example 5

[0074] The difference from Example 4 is that the formula of the binder of the electrode to be tested is different, wherein the weight ratio of sodium carboxymethyl cellulose, styrene-butadiene rubber and polyacrylic acid is 1:2:1, and the remaining steps are the same as Example 4.

[0075] Example 6

[0076] The difference from Example 4 is that the formula of the binder of the electrode to be tested is different, wherein the weight ratio of sodium carboxymethyl cellulose, styrene-butadiene rubber and polyacrylic acid is 1:2:2, and the remaining steps are the same as Example 4.

[0077] The data points corresponding to the weight differences measured in Examples 4 to 6 and the comparison rings are as follows: Figure 3 As shown. Figure 3 It can be seen that the position of the comparison ring corresponding to the adhesive formula of the electrode to be tested in Example 4 is the lowest, indicating that the flexibility of the electrode to be tested in Example 4 is the best; by observing the intersection area of ​​the comparison rings corresponding to Examples 4 to 6, it can be seen that the intersection area of ​​Examples 5 and 6 with Example 4 is smaller, which indicates that compared with Example 4, the flexibility of the electrode to be tested in Examples 5 and 6 is significantly reduced. Therefore, the adhesive formula corresponding to Example 4 is the optimal formula.

[0078] The weight difference data of the electrode pieces to be tested obtained in Examples 1 to 6 of the present application are shown in Table 1; wherein, Δm n refers to m n -m n-1 , when n is 1, Δm1 refers to m1-m0, and so on, Δm2 to Δm5 are obtained in sequence.

[0079] Table 1

[0080] <![CDATA[Δm1]]> <![CDATA[Δm2]]> <![CDATA[Δm3]]> <![CDATA[Δm4]]> <![CDATA[Δm5]]> Example 1 6.53 6.41 6.40 7.08 6.68 Example 2 7.42 6.64 7.20 6.53 6.79 Example 3 7.22 7.06 6.79 7.40 7.60 Example 4 2.66 3.05 2.79 3.26 3.17 Example 5 3.32 3.04 3.40 3.39 3.40 Example 6 3.49 3.25 3.10 3.47 3.69

[0081] Comparative Examples 1 to 3

[0082] A method for testing the flexibility of a negative electrode comprises the following steps:

[0083] The negative electrode sheet prepared in Examples 1 to 3 was used as the electrode sheet to be tested; the electrode sheet to be tested was folded in half, and a 2 kg roller was used to roll back and forth on the surface of the folded electrode sheet for 3 times. Then, the electrode sheet to be tested was laid flat, and the material shedding in the crease area was observed. The more material shedding there was, the worse the flexibility of the electrode sheet to be tested was.

[0084] The material drop conditions of the crease area of ​​the electrode to be tested in Comparative Examples 1 to 3 are as follows: Figure 4 , Figure 5 and 6 As shown. Figure 4 and Figure 5 It can be seen that there is no obvious particle drop in the crease area of ​​the electrode to be tested in Comparative Examples 1 and 2. Figure 6 It can be seen that there is obvious particle falling in the crease area of ​​the electrode to be tested in Comparative Example 3, indicating that its flexibility is worse than that of Comparative Examples 1 and 2.

[0085] The test method for the flexibility of the negative electrode in Comparative Examples 1 to 3 cannot determine the quality of the flexibility of the electrode sheets to be tested in Comparative Examples 1 and 2, nor can it quantitatively determine the difference in flexibility between the electrode sheets to be tested in Comparative Examples 1 to 3.

[0086] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0087] By comparing Examples 1 to 3 and Comparative Examples 1 to 3, it can be seen that the present application uses the weight difference before and after the negative electrode sheet is scraped as an objective indicator to quantify the flexibility of the negative electrode sheet, which can reduce the uncertainty of subjective judgment, and limits the shape of the scraped area each time to the same shape, which can improve the consistency of the test operation process and reduce errors; by analyzing the comparison ring drawn by the data points corresponding to the weight difference, the flexibility of the negative electrode sheet can be quickly and accurately determined, and the difference in flexibility between different negative electrode sheets can also be determined; by quantitatively analyzing the effect of binder formulations with different ratios on the flexibility of the negative electrode sheet, a better binder formulation can be screened out, thereby improving the processability of the negative electrode sheet of the lithium ion battery, and improving the safety and service life of the lithium ion battery.

[0088] By comparing Examples 1 to 6, it can be seen that, compared with other structures, the use of patterned equipment with the above-mentioned structure of the present application for scraping can ensure that the target area for each scraping is the same depth and width, which is beneficial to improve the consistency of the scraping process and reduce operational errors; at the same time, it can also simulate different stress conditions (such as torque, etc.) that the negative electrode sheet may encounter during the preparation process (such as slitting and winding), which is beneficial to provide multiple dimensions for testing the flexibility of the negative electrode sheet, thereby improving the accuracy of the test results.

[0089] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for testing the flexibility of a negative electrode sheet, characterized in that: The test method includes: Step S1, weighing the weight of the electrode piece to be tested, recorded as m0; the electrode piece to be tested includes a negative electrode current collector and a negative electrode active material layer arranged on the surface of the negative electrode current collector, and the material of the negative electrode active material layer includes a binder; Step S2, scraping off a portion of the negative electrode active material layer according to a preset pattern, and weighing the weight of the electrode to be tested after scraping, recorded as m1; Step S3, repeating step S2 for n-1 times, where n≥5, and scraping the same shape area each time to obtain m2 to m n , calculate the weight difference between two consecutive weighings respectively; Step S4, plotting a graph with the formula of the binder as the horizontal axis and the weight difference as the vertical axis, plotting the data points corresponding to the weight difference obtained in step S3 in the graph, and plotting a comparison ring with the absolute value of the difference between the upper limit and the lower limit of the 95% confidence interval of the data point corresponding to each formula as the diameter, and judging the flexibility of the electrode to be tested by analyzing the position of the comparison ring in the graph.

2. The method for testing the flexibility of the negative electrode sheet according to claim 1, characterized in that: The step S2 further includes: placing a patterning device on the surface of the negative electrode active material layer in the electrode to be tested, and using a scratching needle to scrape the negative electrode active material layer.

3. The method for testing the flexibility of the negative electrode sheet according to claim 2, characterized in that: The patterned device has at least one groove structure; Preferably, the number of the groove structures is 5 to 10, and the width is 0.5 to 2 mm.

4. The method for testing the flexibility of the negative electrode sheet according to claim 3, characterized in that: The groove structure is selected from strip grooves and / or arc grooves; Preferably, the length of the strip groove is 3 to 10 cm, and the arc groove is a semicircular groove, and more preferably, its radius is 2 to 5 cm; Preferably, the material of the patterned chemical clothing is selected from polymethyl methacrylate and / or polytetrafluoroethylene.

5. The method for testing the flexibility of a negative electrode sheet according to any one of claims 1 to 4, characterized in that: The shape of the electrode piece to be tested is a rectangle or a square, with a length of 7 to 20 cm, a width of 7 to 20 cm, or a side length of 7 to 20 cm.

6. The method for testing the flexibility of the negative electrode sheet according to claim 2, characterized in that: The difference in flexibility of the pole pieces to be tested is determined by analyzing the intersection area of ​​the comparison rings corresponding to the two pole pieces to be tested.

7. The method for testing the flexibility of the negative electrode sheet according to claim 3, characterized in that: The scribing needle has a conical tip, and the diameter of the tip does not exceed the width of the groove structure; Preferably, the material of the scribing needle is selected from stainless steel and / or aluminum.

8. The method for testing the flexibility of a negative electrode sheet according to any one of claims 1 to 7, characterized in that: The step S2 also includes: using an ear cleaning ball to remove the scraped powder; preferably, the removal process includes: blowing along the scraping direction of the electrode to be tested for 3 to 5 times, and then blowing perpendicular to the scraping direction for 3 to 5 times.

9. The method for testing the flexibility of a negative electrode sheet according to any one of claims 1 to 8, characterized in that: The comparison ring is drawn using data analysis software, preferably the data analysis software is JMP software, and the variance analysis function in the JMP software is used to draw the comparison ring.

10. The method for testing the flexibility of a negative electrode sheet according to any one of claims 1 to 8, characterized in that: The surface density of the negative electrode active material layer in the electrode to be tested is 5 to 15 mg / cm 2 , compacted density is 1~1.7mg / cm 3 .

Citation Information

Patent Citations

  • Detection method for flexibility of lithium ion battery pole piece

    CN105406142A

  • Lithium ion battery pole piece adhesive power testing method

    CN110398457A

  • Method for evaluating performance of negative electrode binder

    CN111579412A

  • Method for detecting flexibility of lithium ion battery electrode sheet

    CN113237828A

  • Simple and convenient evaluation method for flexibility of lithium battery pole piece

    CN115876589A